Customer Satisfaction with Online Food Delivery Services - Suhardjo, Suhardjo; Renaldo, Nicholas; Sevendy, Tandy; Wahid, Nabila; Cecilia, Cecilia (Luxury: Landscape of Business Administration, 2023)
The rapid growth of online food delivery services in Indonesia, especially in Pekanbaru, has led to changes in consumer behavior. As a result, companies need to focus on various factors that can enhance customer satisfaction. This study investigates how service quality, promotional activities, and the user-friendliness of the delivery app impact customer satisfaction within this context. Sampling was conducted using a non-probability technique due to the unequal opportunity for all individuals to be part of the sample. The Roscoe approach was used to determine the sample size, resulting in 150 respondents. Data was collected through a questionnaire using a 5-point Likert scale, and analysis was performed using multiple linear regression and the SPSS 21 software. The findings of the study demonstrate that service quality, promotions, and ease of using the app all have a significant influence on customer satisfaction.